Semantic analysis of milk components in Surah Al-Nahl verse 66 and Al-Mu’Minun verse 21 - Abdul Qudus Al Faruq,; Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
According to modern scientists, milk must be boiled first to eliminate bacteria, as it is produced alongside blood and food in the animal's body. Interestingly, this concept was introduced earlier in the Qur'an, specifically in Surah An-Nahl (16:66) and Surah Al-Mu’minun (23:21), which discuss the composition and formation of milk within the animal's body using subtle language that requires deeper analysis. This study aims to explore the components and formation stages of milk through a Semantic and Scientific approach. The research employs a descriptive-analytical method using an interdisciplinary approach that combines semantics and science. For linguistic analysis, the study uses the theories of derivation (isytiqaq) and context (siyaq) to analyze the Qur'anic text and is based on library research. The study concludes that the Qur'an accurately describes the composition of milk in these two verses, indicating that milk is produced alongside blood in the stomach but remains uncontaminated. However, it still requires boiling to eliminate bacteria. The study also highlights the nutritional benefits of milk for human health, demonstrating that these insights existed long before modern scientific discoveries.